Totalisation et parcours - Marie-Line Groussier (Corela)
Totalization and scanning are two operations of enunciative determination in A. Culioli’s theory. Should totalization be considered to be always associated with scanning? When one lists the notions expressed by the various roots whose reflexes appear in totalization markers and scanning markers in I.-E. languages, these notions are found to be few on account of some interesting phenomena of convergence. In most cases, totalization markers are clearly distinguishable from scanning markers, quantity being preponderant in totalization, quality in scanning. Yet, inversions of preponderance will happen, resulting from the essential lability of natural languages.Thus, a totalization marker, like Fr. tout can mark scanning in a sentence like out homme est mortel.